The effectivity of Omega-3 Fatty Acids in Medical Nutrition Therapy for Critically Illness - Ristiana Suci (Journal of Social Research, 2025)
Malnutrition is a common problem found in hospitals and has a serious impact on the patient's healing process, which can increase morbidity and mortality rates, contributing to prolonged length of stay and increased treatment costs. Therefore, nutritional support is needed to prevent malnutrition and further complications, such as nutrition containing the polyunsaturated omega 3 fatty acids, known as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). These fatty acids have anti-inflammatory, immunomodulatory, and antioxidant effects that have the potential to increase immunity and repair damaged tissue and help to maintain muscle mass and strength. The purpose of this literature study is to evaluate the effect of providing nutrition containing omega-3, both enterally and parenterally, on the healing process of patients with critical illness. The design in this study is a literature review of research sources using Randomized Controlled Trials (RCTs) and cohorts. From the results of this literature study, it can be concluded that nutrition containing omega 3 has an effect on accelerating the healing of patients with critical illnesses and reducing the risk of complications, thereby shortening the length of stay in the ICU.